2014
DOI: 10.1111/jir.12123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between living arrangement and adherence to antiepileptic medications among individuals with developmental disabilities

Abstract: Non-adherence to AEDs is a potential medical risk for individuals with ID that is significantly impacted by the type of community living arrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In the USA, living situation was found to be associated with adherence to AEDs, with non‐adherence being 6% in group homes, 20% in semi‐independent living and 32% in family homes (Hom et al . ). In Ireland, those in residential care were more likely to have a seizure diary (93%) than those living independently (44%) or in the community (78%) (McCarron et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the USA, living situation was found to be associated with adherence to AEDs, with non‐adherence being 6% in group homes, 20% in semi‐independent living and 32% in family homes (Hom et al . ). In Ireland, those in residential care were more likely to have a seizure diary (93%) than those living independently (44%) or in the community (78%) (McCarron et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Hom et al . ), and in one survey, most respondents were from the United States (USA) (Camfield et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Semiindependent living arrangements were also negative predictors of adherence in those with intellectual disabilities compared with those in a group home setting. 50 Guardians of children with DS may also influence therapy. One study reported that guardians of children with intellectual disabilities were more likely to refuse to vaccinate them.…”
Section: Social Considerationsmentioning
confidence: 97%
“…It has been reported that individuals with intellectual disabilities (including DS) living in a family home displayed higher rates of nonadherence to medication regimens compared with those in group homes . Semi‐independent living arrangements were also negative predictors of adherence in those with intellectual disabilities compared with those in a group home setting . Guardians of children with DS may also influence therapy.…”
Section: Social Considerationsmentioning
confidence: 99%